Appropriate amount of modified corn flour improves the structural and physicochemical properties of wheat dough - Mengdi Song; Zhiqiang Fan; Zhan Liang; Shihong Wang; Xing Zhang; Youqiang Pei; Haiyan Gao; Jie Zeng (Food Chemistry: X)
This study investigated effects of superfine grinding modified corn flour (SG-CF) and hot blanching modified corn flour (HB-CF) on properties of wheat flour and dough to improve the suitability of corn flour in flour products. Results indicated that the addition of SG-CF or HB-CF reduced the moisture and protein content of the mixed flour, and increased the dietary fiber content and free water proportion. Compared with SG-CF, HB-CF was more helpful enhancing the thermal stability and anti-aging properties of the mixed flour. When the amount of SG-CF was less than 15 % or the amount of HB-CF was less than 20 %, the texture properties and microstructure of the wheat dough was maintained. However, the excessive addition of SG-CF or HB-CF destroyed the gluten network structure. Results of this study are expected to provide valuable guidance for the application of SG-CF and HB-CF in flour-based products.